MASALAH PELAKSANAAN EKSEKUSI HARTA PERKAWINAN MENURUT SISTEM HUKUM INDONESIA DAN MALAYSIA: The Problem of Executing Marital Property According to the Indonesian and Malaysian Legal System - Geraldus Thenys Kurnia Manik Raja; Ning Adiasih (Faculty of Law, Universitas Trisakti, 2025)
The regulation of polemics regarding the division of post-divorce joint property is different in the jurisdictions of Indonesia and Malaysia. This study discusses the procedure and the advantages and disadvantages of executing marital property in both legal systems. Using a normative legal research method with a comparative legal approach, this study qualitatively analyzes secondary data to produce descriptive data and draw deductive conclusions. The results show that Indonesia has a structured execution procedure in the Religious Court, though it is constrained by the complexity of customary land practices and issues. Meanwhile, Malaysia's Syariah Court offers diverse enforcement mechanisms and emphasizes mediation; however, it faces jurisdictional fragmentation and difficulties proving non-financial contributions. In conclusion, both systems have unique advantages and challenges in ensuring the fairness of post-divorce property division.